Convergence and Determinants of Health Development in North Sumatera Province - Ing Mariani Hastuti; Wiwiek Rindayati; Alla Asmara (Signifikan: Jurnal Ilmu Ekonomi, 2022)
Health contributes to increasing productivity in generating quality human resources. Health development aims to attain the highest public health degree fairly and equally. Convergence reduces the gap between regions and makes development more equitable. One of the booming health development indicators is life expectancy. The government must collaborate across sectors, namely the social and economic sectors, to accelerate the convergence process. This study aims to identify convergence and analyze the determinants of health development in North Sumatera Province. To this purpose, panel data of 33 districts/cities in North Sumatera Province over 2012-2019 is investigated using the Generalized Method of Moment (GMM) as dynamic panel data analysis. The results showed that convergence in health development measured by life expectancy occurred in North Sumatera Province. The most influential variables in health development were socio-economic variables.How to Cite:Hastuti, I. M., Rindayati, W., & Asmara, A. (2022). Convergence and Determinants of Health Development in North Sumatera Province. Signifikan: Jurnal Ilmu Ekonomi, 11(1), 161-174. https://doi.org/10.15408/sjie.v11i1.20576.